Eksperimentasi Model STAD Flipped Classroom Media Edmodo Terhadap Prestasi Belajar Ditinjau dari Motivasi Belajar - Wahyu Dewi; sasomo budi; Arum Rahmawati (Universitas Sarjanawiyata Tamansiswa, 2022)
The purpose of this study was to determine the effect of the learning model on mathematics learning achievement and to determine the effect of learning motivation on students' mathematics learning achievement, and whether there is an interaction between the three variables. This research design uses a quasi-experimental design with a sampling technique that is cluster random sampling. Based on the hypothesis test using the two-way ANOVA test, three hypothetical decisions were obtained: 1) The results of the first hypothesis test stated the value of Fcount > Ftable (10.01 > 3.99), so H0 was rejected in other words the learning model affected learning achievement, through the post-anava test. the results obtained Fcount > Ftable (13.29 > 7.98), it can be concluded that the learning model in the experimental class produces better learning achievement than the learning model in the control class; 2) The results of the second hypothesis test state that Fcount > Ftable (24.98 > 3.14), so H0 is rejected, in other words, students' motivation to learn mathematics affects their learning achievement. Based on the post-anava test, it was found that high and medium students' motivation to learn mathematics resulted in better learning achievement than students with low mathematics learning motivation; 3) The result of the third hypothesis test states that Fcount > Ftable (0.22 < 3.14) then H0 is accepted, in other words there is no interaction between the learning model and the motivation to learn mathematics on students' mathematics learning achievement.